Influenza Infection in Mice Induces Accumulation of Lung Mast Cells through the Recruitment and Maturation of Mast Cell Progenitors - Zarnegar, Behdad; Mendez-Enriquez, Erika; Westin, Annika; Söderberg, Cecilia; Dahlin, Joakim S.; Grönvik, Kjell-Olov; Hallgren, Jenny (Frontiers in Immunology, 2017)
Mast cells (MCs) are powerful immune cells that mature in the peripheral tissues from bone marrow (BM)-derived mast cell progenitors (MCp). Accumulation of MCs in lung compartments where they are normally absent is thought to enhance symptoms in asthma. The enrichment of lung MCs is also observed in mice subjected to models of allergic airway inflammation. However, whether other types of lung inflammation trigger increased number of MCp, which give rise to MCs, is unknown. Here, mouse-adapted H1N1 influenza A was used as a model of respiratory virus infection. Intranasal administration of the virus induced expression of VCAM-1 on the lung vascular endothelium and an extensive increase in integrin β7hi lung MCp. Experiments were performed to distinguish whether the influenza-induced increase in the number of lung MCp was triggered mainly by recruitment or in situ cell proliferation. A similar proportion of lung MCp from influenza-infected and PBS control mice were found to be in a proliferative state. Furthermore, BM chimeric mice were used in which the possibility of influenza-induced in situ cell proliferation of host MCp was prevented. Influenza infection in the chimeric mice induced a similar number of lung MCp as in normal mice. These experiments demonstrated that recruitment of MCp to the lung is the major mechanism behind the influenza-induced increase in lung MCp. Fifteen days post-infection, the influenza infection had elicited an immature MC population expressing intermediate levels of integrin β7, which was absent in controls. At the same time point, an increased number of toluidine blue+ MCs was detected in the upper central airways. When the inflammation was resolved, the MCs that accumulated in the lung upon influenza infection were gradually lost. In summary, our study reveals that influenza infection induces a transient accumulation of lung MCs through the recruitment and maturation of MCp. We speculate that temporary augmented numbers of lung MCs are a cause behind virus-induced exacerbations of MC-related lung diseases such as asthma.